Justice for kids : keeping kids out of the juvenile justice system - Dowd, Nancy E., 1949- (Families, law, and society series., 2011)
Children and youth become involved with the juvenile justice system at a significant rate. While some children move just as quickly out of the system and go on to live productive lives as adults, other children become enmeshed in the system, developing deeper problems and/or transferring into the adult criminal justice system. Justice for Kids is a volume of work by leading academics and activists that focuses on ways to intervene at the earliest possible point to rehabilitate and redirectoto keep kids out of the systemorather than to punish and drive kids deeper. Justice for Kids presents a c.